Find the information you're looking for at Westonci.ca, the trusted Q&A platform with a community of knowledgeable experts. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To solve the equation [tex]\( x^4 - 17x^2 + 16 = 0 \)[/tex], we can use a substitution to simplify the problem.
1. Substitute:
Let [tex]\( u = x^2 \)[/tex].
This means [tex]\( u^2 = (x^2)^2 = x^4 \)[/tex].
2. Rewrite the equation:
Substitute [tex]\( u \)[/tex] into the original equation:
[tex]\[ x^4 - 17x^2 + 16 = 0 \implies u^2 - 17u + 16 = 0 \][/tex]
Now, we have a quadratic equation in terms of [tex]\( u \)[/tex].
3. Solve the quadratic equation:
To solve [tex]\( u^2 - 17u + 16 = 0 \)[/tex], we can use the quadratic formula [tex]\( u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = -17 \)[/tex], and [tex]\( c = 16 \)[/tex].
- Calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac = (-17)^2 - 4 \cdot 1 \cdot 16 = 289 - 64 = 225 \][/tex]
- Find the solutions for [tex]\( u \)[/tex]:
[tex]\[ u_1 = \frac{17 + \sqrt{225}}{2 \cdot 1} = \frac{17 + 15}{2} = \frac{32}{2} = 16 \][/tex]
[tex]\[ u_2 = \frac{17 - \sqrt{225}}{2 \cdot 1} = \frac{17 - 15}{2} = \frac{2}{2} = 1 \][/tex]
4. Back-substitute to find [tex]\( x \)[/tex]:
Since [tex]\( u = x^2 \)[/tex], we need to solve for [tex]\( x \)[/tex]:
- For [tex]\( u_1 = 16 \)[/tex]:
[tex]\[ x^2 = 16 \implies x = \pm \sqrt{16} = \pm 4 \][/tex]
- For [tex]\( u_2 = 1 \)[/tex]:
[tex]\[ x^2 = 1 \implies x = \pm \sqrt{1} = \pm 1 \][/tex]
5. List all solutions:
The solutions to the original equation [tex]\( x^4 - 17x^2 + 16 = 0 \)[/tex] are:
[tex]\[ x = 4, -4, 1, -1 \][/tex]
So, the complete set of solutions is:
[tex]\[ x = \{4, -4, 1, -1\} \][/tex]
1. Substitute:
Let [tex]\( u = x^2 \)[/tex].
This means [tex]\( u^2 = (x^2)^2 = x^4 \)[/tex].
2. Rewrite the equation:
Substitute [tex]\( u \)[/tex] into the original equation:
[tex]\[ x^4 - 17x^2 + 16 = 0 \implies u^2 - 17u + 16 = 0 \][/tex]
Now, we have a quadratic equation in terms of [tex]\( u \)[/tex].
3. Solve the quadratic equation:
To solve [tex]\( u^2 - 17u + 16 = 0 \)[/tex], we can use the quadratic formula [tex]\( u = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1 \)[/tex], [tex]\( b = -17 \)[/tex], and [tex]\( c = 16 \)[/tex].
- Calculate the discriminant:
[tex]\[ \Delta = b^2 - 4ac = (-17)^2 - 4 \cdot 1 \cdot 16 = 289 - 64 = 225 \][/tex]
- Find the solutions for [tex]\( u \)[/tex]:
[tex]\[ u_1 = \frac{17 + \sqrt{225}}{2 \cdot 1} = \frac{17 + 15}{2} = \frac{32}{2} = 16 \][/tex]
[tex]\[ u_2 = \frac{17 - \sqrt{225}}{2 \cdot 1} = \frac{17 - 15}{2} = \frac{2}{2} = 1 \][/tex]
4. Back-substitute to find [tex]\( x \)[/tex]:
Since [tex]\( u = x^2 \)[/tex], we need to solve for [tex]\( x \)[/tex]:
- For [tex]\( u_1 = 16 \)[/tex]:
[tex]\[ x^2 = 16 \implies x = \pm \sqrt{16} = \pm 4 \][/tex]
- For [tex]\( u_2 = 1 \)[/tex]:
[tex]\[ x^2 = 1 \implies x = \pm \sqrt{1} = \pm 1 \][/tex]
5. List all solutions:
The solutions to the original equation [tex]\( x^4 - 17x^2 + 16 = 0 \)[/tex] are:
[tex]\[ x = 4, -4, 1, -1 \][/tex]
So, the complete set of solutions is:
[tex]\[ x = \{4, -4, 1, -1\} \][/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.